Pendidikan Kesehatan Efektif untuk Mendorong Perilaku Wanita Usia Subur dalam Mengikuti Deteksi Dini Kanker Leher Rahim - Eki Dwi Ariani; Runjati Runjati; Ari Suwondo (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Cervical cancer is a primary malignant neoplasm caused by persistent oncogenic Human Papilloma Virus. The purpose of this literature review was to determine the effectiveness of health education to improve the behavior of women of childbearing age to participate in early detection of cervical cancer. This study was a systematic review with the PRISMA approach using the PICO strategy including: 1) Population: women of childbearing age; 2) Intervention: health education; 3) Comparison: none; 4) Outcome: participating in early detection of cervical cancer. This study used one database, namely Google Scholar. The inclusion criteria used were: full-text articles, published in Indonesian or English, with the research subjects being women of childbearing age. The exclusion criteria were: articles published more than five years ago. This study obtained 5 articles that met the criteria. The results of the synthesis showed that the health education methods used included: lectures, audiovisuals, leaflets and booklets. All of these health education methods could improve the knowledge and attitudes of respondents. Furthermore, it was concluded that health education is effective in improving the knowledge and attitudes of women of childbearing age to participate in early detection of cervical cancer.Keywords: cervical cancer; women of childbearing age; early detection; health education; knowledge; attitude ABSTRAK Kanker leher rahim merupakan neoplasma ganas primer yang disebabkan oleh Human Papilloma Virus onkogenik yang persisten. Tujuan dari tinjauan literatur ini adalah mengetahui efektivitas pendidikan kesehatan untuk meningkatkan perilaku wanita usia subur guna mengikuti deteksi dini kanker leher rahim. Studi ini merupakan tinjauan sistematis dengan pendekatan PRISMA yang menggunakan strategi PICO meliputi: 1) Population: wanita usia subur; 2) Intervention: pendidikan kesehatan; 3) Comparation: tidak ada; 4) Outcome: mengikuti deteksi dini kanker leher rahim. Studi ini menggunakan satu database yaitu Google Scholar. Kriteria inklusi yang digunakan adalah: artikel teks penuh, diterbitkan dalam bahasa Indonesia atau bahasa Inggris, dengan subjek penelitian adalah wanita usia subur. Kriteria eksklusi adalah: artikel yang diterbitkan lebih dari lima tahun. Studi ini mendapatkan 5 artikel yang sesuai dengan kriteria. Hasil sintesis menunjukkan bahwa metode pendidikan kesehatan yang digunakan antara lain: ceramah, audiovisual, leaflet dan booklet. Semua metode pendidikan kesehatan tersebut dapat meningkatkan pengetahuan dan sikap para responden. Selanjutnya disimpulkan bahwa pendidikan kesehatan efektif untuk meningkatkan pengetahuan dan sikap wanita usia subur guna mengikuti deteksi dini kanker leher rahim. Kata kunci: kanker leher rahim; wanita usia subur; deteksi dini; pendidikan kesehatan; pengetahuan; sikap